1980
DOI: 10.1084/jem.151.5.1183
|View full text |Cite
|
Sign up to set email alerts
|

Antigen- and receptor-driven regulatory mechanisms. IV. Idiotype-bearing I-J+ suppressor T cell factors induce second-order suppressor T cells which express anti-idiotypic receptors.

Abstract: Regulation of the immune response to antigen involves the interactions of many cell types. There is substantial evidence attesting to the decisive role of suppressor T cells in the inhibition of both humoral (1) and cell-mediated (2) immune reactivity to a variety of antigens. In addition, regulatory molecules derived from such suppressor T cells have been identified in a number of experimental systems (reviewed in 3, 4).Suppressor T cells (Ts) 1 operative in regulating responses to many antigens have been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(66 citation statements)
references
References 30 publications
6
60
0
Order By: Relevance
“…Studies from other laboratories have also demonstrated anti-idiotypic T cells involved in helper (21,22,(25)(26)(27) and suppressor (28)(29)(30)(31)(32)(33) cell activity. It might be envisioned that the anti-idiotypic T cell population could be divided into two distinct groups based on differences in the immunization procedures used to induce these cells and ultimately on differences in the specificity of the T ceils.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other laboratories have also demonstrated anti-idiotypic T cells involved in helper (21,22,(25)(26)(27) and suppressor (28)(29)(30)(31)(32)(33) cell activity. It might be envisioned that the anti-idiotypic T cell population could be divided into two distinct groups based on differences in the immunization procedures used to induce these cells and ultimately on differences in the specificity of the T ceils.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, interaction of target cells with T-helper (2-5) or T suppressor (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) cells may depend on recognition of unique idiotypic determinants on the surface of the target cell. Furthermore, these interactions may be mediated by regulatory molecules that either bear the idiotype themselves (10,(15)(16)(17)(18) or are idiotype specific (10).…”
mentioning
confidence: 99%
“…It is possible that T cells in the normal spleen cell population interact with the antigenspecific immune spleen cells to generate idiotype-specific suppressor T cells (21). It is known that Ig-associated structures on activated B cells can trigger Ly-1+2 -inducer cells to stimulate Ly-2 ÷ T suppressor activity (22).…”
Section: Discussionmentioning
confidence: 99%